Occupational Mobility and Wage Inequality - Gueorgui Kambourov; Iourii Manovskii (Institute for the Study of Labor (IZA), 2004)
In this study we argue that wage inequality and occupational mobility are intimately related. We are motivated by our empirical findings that human capital is occupation-specific and that the fraction of workers switching occupations in the United States was as high as 16% a year in the early 1970s and had increased to 19% by the early 1990s. We develop a general equilibrium model with occupation-specific human capital and heterogeneous experience levels within occupations. We argue that the increase in occupational mobility was due to the increase in the variability of productivity shocks to occupations. The model, calibrated to match the increase in occupational mobility, accounts for over 90% of the increase in wage inequality over the period. A distinguishing feature of the theory is that it accounts for changes in within-group wage inequality and the increase in the variability of transitory earnings.
Keywords: J31; E24; J62; E25; E20; J24; 330; occupational mobility; wage inequality; within-group inequality; human capital; sectoral reallocation; Arbeitsmobilität; Lohnstruktur; Humankapital; Sektorale Beschäftigungsstruktur; Schätzung; Vereinigte Staaten